Huey P. Newton prelude to revolution - Evans, John.; Newton, Huey P.; Xenon Pictures; Lions Gate Entertainment (Firm) (Santa Monica, CA : Lionsgate, 2009)
Huey P. Newton was a co-founder of the Black Panther Party for Self-Defense, and origanization FBI director J. Edgar Hoover once called 'the greatest internal threat to the security of the United States.' Newton spent four years in prison for the voluntary manslaughter of an Oakland police officer before his conviction was overturned in 1971. Newton discusses his goals as a revolutionary, including self-determination for African-Americans, full employment, decent housing for the poor and disenfranchised, an end to police brutality, and an end to the Vietnam War.
Documentary.
DVD, full screen (1.33:1); Dolby Digital 2.0 stereo.
Title from container.
Interviews with Huey P. Newton and director John Evans.
Not rated.
Keywords: Newton, Huey P; Black Panther Party; Manslaughter -- California -- Oakland; Revolutionaries -- United States; Black militant organizations -- United States; Documentary films